2018
DOI: 10.1017/gmh.2018.18
|View full text |Cite
|
Sign up to set email alerts
|

Does mhGAP training of primary health care providers improve the identification of child- and adolescent mental, neurological or substance use disorders? Results from a randomized controlled trial in Uganda

Abstract: Background.Integrating child and adolescent mental health (CAMH) into primary health care (PHC) using the WHO mental health gap action program (mhGAP) is recommended for closing a mental health treatment gap in low- and middle-income countries, but PHC providers have limited ability to detect CAMH disorders. We aimed to evaluate the effect of PHC provider mhGAP training on CAMH disorder identification in Eastern Uganda.Methods.Thirty-six PHC clinics participated in a randomized controlled trial which compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 37 publications
0
36
0
Order By: Relevance
“…There is a need to increase collaboration between the traditional and biomedical sectors of mental health care to improve access to CAMHS Traditional healers should be able to recognize and refer children with mental health issues to CAMHS Akol et al 2015 [ 18 ] Kampala and Mbale, Eastern Uganda To explore strengths and weaknesses of CAMHS at national and district levels from a management perspective Semi-structured interviews with 7 public officials responsible for management and supervision of CAMHS at national level (Kampala) and district level (Mbale) Inadequate national mental health policies, inadequate Child and adolescent mental health financing and services; a solution is to integrate child and adolescent mental health into primary health care and other sectors CAMHS absent at lower-level health centres (primary health care centres) Insufficient CAMHS workforce should be increased by both in-service and pre-service training Health management information systems are insufficient for service planning Okello et al 2014 [ 19 ] Northern and Central Uganda To explore the mental health of young people in secondary schools in Northern and Central Uganda Focus group discussions with 78 13–24-year-olds from 4 secondary schools, former child soldiers There are key gaps in the knowledge and attitudes of young people (i.e., lack of knowledge about common mental health disorders, early signs of reduced functioning and poor mental health, and the link between substance use and mental illness) that need to be targeted by mental health interventions focused on young people B. Quantitative Studies Kivumbi et al 2019 [ 20 ] Uganda To examine the effect of participating in a family-based economic strengthening intervention (child development account, mentorship programme and workshops on financial management and microenterprise development) on the mental health wellbeing of female adolescent orphans impacted by HIV/AIDS in rural Uganda Randomized trial consisting of female orphans aged 10–16 years. Intervention group (n = 516) received economic empowerment intervention in addition to standard care services for orphans, while control group (n = 273) received only standard care services Improvement in mental health functioning over time among female participants receiving the economic empowerment intervention Akol et al 2018 [ 21 ] Mbale and Sironko districts, Eastern Uganda To evaluate the effect of primary health care provider mhGAP training on the identification and treatment of CAMH disorders Randomized controlled trial. Intervention group (n = 18) clinics received mhGAP-o...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There is a need to increase collaboration between the traditional and biomedical sectors of mental health care to improve access to CAMHS Traditional healers should be able to recognize and refer children with mental health issues to CAMHS Akol et al 2015 [ 18 ] Kampala and Mbale, Eastern Uganda To explore strengths and weaknesses of CAMHS at national and district levels from a management perspective Semi-structured interviews with 7 public officials responsible for management and supervision of CAMHS at national level (Kampala) and district level (Mbale) Inadequate national mental health policies, inadequate Child and adolescent mental health financing and services; a solution is to integrate child and adolescent mental health into primary health care and other sectors CAMHS absent at lower-level health centres (primary health care centres) Insufficient CAMHS workforce should be increased by both in-service and pre-service training Health management information systems are insufficient for service planning Okello et al 2014 [ 19 ] Northern and Central Uganda To explore the mental health of young people in secondary schools in Northern and Central Uganda Focus group discussions with 78 13–24-year-olds from 4 secondary schools, former child soldiers There are key gaps in the knowledge and attitudes of young people (i.e., lack of knowledge about common mental health disorders, early signs of reduced functioning and poor mental health, and the link between substance use and mental illness) that need to be targeted by mental health interventions focused on young people B. Quantitative Studies Kivumbi et al 2019 [ 20 ] Uganda To examine the effect of participating in a family-based economic strengthening intervention (child development account, mentorship programme and workshops on financial management and microenterprise development) on the mental health wellbeing of female adolescent orphans impacted by HIV/AIDS in rural Uganda Randomized trial consisting of female orphans aged 10–16 years. Intervention group (n = 516) received economic empowerment intervention in addition to standard care services for orphans, while control group (n = 273) received only standard care services Improvement in mental health functioning over time among female participants receiving the economic empowerment intervention Akol et al 2018 [ 21 ] Mbale and Sironko districts, Eastern Uganda To evaluate the effect of primary health care provider mhGAP training on the identification and treatment of CAMH disorders Randomized controlled trial. Intervention group (n = 18) clinics received mhGAP-o...…”
Section: Resultsmentioning
confidence: 99%
“…The services available are affected by issues of understaffing and low capacity; thus, there was a need described for an upgrade of both both human resources and service facilities [ 16 ]. Currently, there are only five child psychiatrists in the whole country, compared with one traditional healer per 500 inhabitants to whom patients tend to turn instead [ 17 , 21 ] (Table 1 ). Further task-sharing and in-service and pre-service training was described urgently needed, as this could help to integrate CAMHS into primary health care [ 22 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent systematic analysis, the PRogramme for Improving MEntal health care (PRIME) and its sister study 'emerging mental health systems in LMIC Study' (EMERALD) program, found mhGAP IG materials when properly integrated into a comprehensive integrated mental health services package can improve mental health services in LMIC (Keynejad et al, 2018;Petersen et al, 2019). Researchers in Uganda assessed the effect of integrating the mhGAP IG modules for CAMH and they found a trend towards improved detection of MNS disorders (Akol et al, 2018). International Association of Child and Adolescent Psychiatry and Allied Professions (IACAPAP) has free online courses on child and adolescent mental health and has developed a e-textbook and slides that when used with the mhGAP training materials results in increased knowledge among non-mental health specialists (Akol et al, 2017).…”
Section: Paediatricians and Primary Care Physiciansmentioning
confidence: 99%